Revitalisasi Metode Mudzakarah dalam Meningkatkan Pembelajaran yang Interaktif - Irfan Maulana Adnan (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2025)
This research discusses the revitalization of the mudzakarah method to enhance interactive learning for students. The mudzakarah method is a teaching technique based on two-way discussions aimed at deepening understanding and increasing student engagement through the exchange of opinions. With a descriptive qualitative approach based on literature studies, this research explores how this method can be effectively applied. The research results show that the implementation of structured discussions, clear guidelines, and open communication can encourage student participation, enhance critical and collaborative thinking skills, and motivate them in learning. However, there are Challenges, such as the lack of understanding of the discussion concept by students, which can be addressed through the role of the teacher as a facilitator and motivator. This way, their opinions feel valued and they are more motivated to engage actively, creating an interactive learning atmosphere.